1999
DOI: 10.1111/j.1600-0773.1999.tb00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Ion Channel Control pH6‐Induced Bronchoconstriction and Calcitonin Gene‐Related Peptide Release in the Guinea‐Pig Lung

Abstract: Abstrrrcr:We have studied the bronchoconstriction and the release of calcitonin gene-related peptide-like immunoreactivity induced by perfusion of pH6 buffer in the isolated guinea-pig perfused lung. Both bronchoconstriction and peptide release were completely abolished after systemic capsaicin pretreatment. Ca2+-free pH6 buffer infusion also completely inhibited the bronchial response, whereas the calcitonin gene-related peptide-like immunoreactivity overflow was significantly reduced. w-Conotoxine and w-agat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In addition, previous studies showed that caffeine may have protective and nutritive effects on neurons to prevent and treat Parkinson's disease and migraine; stimulate release of calcitonin gene-related peptide [26] , which is recognized as one of the most important sensory neurotrans-ducers and neuromodulators in the bladder to improve the impaired sensation of bladder fullness in diabetic rats [27] ; and influence neuromuscular functions as the antagonist of adenosine receptors in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous studies showed that caffeine may have protective and nutritive effects on neurons to prevent and treat Parkinson's disease and migraine; stimulate release of calcitonin gene-related peptide [26] , which is recognized as one of the most important sensory neurotrans-ducers and neuromodulators in the bladder to improve the impaired sensation of bladder fullness in diabetic rats [27] ; and influence neuromuscular functions as the antagonist of adenosine receptors in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…As was stated above, we suggest that the mechanism for the effect on the bladder is as follows: (i) by increasing cAMP content in the bladder recovery of the micturition reflex and improvement of the detrusor contractility was shown; (ii) during the storage phase, caffeine may reduce spontaneous contraction overactivity in a detrusor instability model [21] , and thus benefits bladder compliance; (iii) histopathological studies showed that caffeine could protect the ultrastructures of intracellular sarcoplasmic reticulum, mitochondria, and so on, in the bladder muscle of diabetic rats (unpublished our data). In addition, previous studies showed that caffeine may have protective and nutritive effects on neurons to prevent and treat Parkinson's disease and migraine; stimulate release of calcitonin gene-related peptide [26] , which is recognized as one of the most important sensory neurotrans-ducers and neuromodulators in the bladder to improve the impaired sensation of bladder fullness in diabetic rats [27] ; and influence neuromuscular functions as the antagonist of adenosine receptors in vivo.…”
Section: Discussionmentioning
confidence: 99%